Power generation, operation, and control. - Wood, Allen J.; Wollenberg, Bruce F.; Sheblé, Gerald B. (Wiley-IEEE, 2013)
"Since publication of the second edition, there have been extensive changes in the algorithms, methods, and assumptions in energy management systems that analyze and control power generation. This edition is updated to acquaint electrical engineering students and professionals with current power generation systems. Algorithms and methods for solving integrated economic, network, and generating system analysis are provided. Also included are the state-of-the-art topics undergoing evolutionary change, including market simulation, multiple market analysis, multiple interchange contract analysis, contract and market bidding, and asset valuation under various portfolio combinations"-- Provided by publisher.
Keywords: Electric power systems.; elektronické knihy; electronic books